Fragmented skeletonised remains: Paget's disease as a method of biological profiling using radiography. (March 2023) - Elliott, James; Stark, Sarah; Teoaca, Adelina; Duffy, Elizabeth; Williams, Eleanor
Highlights: Primary evidence is not always available with fragmented, skeletal remains for identification efforts. This archaeological example demonstrates secondary evidence collection with radiography. Diagnosis of Paget's disease corroborates with biological profile of adult male and suggests white (British) ethnicity. Forensic radiography, complemented with photography, may yield useful secondary evidence. Abstract: Background: This study presents the incidental finding of Paget's disease within archaeological skeletal remains using radiography. The remains of a late medieval (14 th -15 th century AD) adult male were excavated in 2017 from St Albans Monks' Graveyard, Hertfordshire, United Kingdom. Upon visual inspection the skeleton exhibited widespread changes suggestive of Paget's disease which prompted the radiographic investigation. The resultant imaging demonstrated an expanded bone and coarse trabecular patterns characteristic of the pathology. Discussion: Forensic radiography provides valuable information for the reconstruction of biological profiles of the deceased for victim identification. Characteristic medical conditions such as Paget's disease aid identification by excluding unaffected persons, as the pathology exhibits a higher prevalence among British white males of advanced age. This example, although archaeological in origin, illustrates how data available from human skeletal remains can be leveraged through radiographic imaging to glean biographical information which might otherwise be unavailable. In the presence of fragmentary skeletal remains, and the absence of DNA profiling, pathologies with characteristic radiographic appearances could be of forensic significance. Conclusion: This example demonstrates the radiographic appearances of Paget's disease on fragmentary skeletal remains which may aid victim identification efforts. Consideration must be given to the limitations of Paget's disease including anthropological estimations and the potential for alternative diagnoses. Lastly, radiography may offer an accurate, permanent record of the deceased as secondary evidence for identification efforts.